2003
DOI: 10.1590/s0100-879x2003001200009
|View full text |Cite
|
Sign up to set email alerts
|

c-Fos expression induced by electroacupuncture at the Zusanli point in rats submitted to repeated immobilization

Abstract: In laboratory animals, acupuncture needs to be performed on either anesthetized or, if unanesthetized, restrained subjects. Both procedures up-regulate c-Fos expression in several areas of the central nervous system, representing therefore a major pitfall for the assessment of c-Fos expression induced by electroacupuncture. Thus, in order to reduce the effect of acute restraint we used a protocol of repeated restraint for the assessment of the brain areas activated by electroacupuncture in adult male Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 33 publications
(32 reference statements)
4
17
0
Order By: Relevance
“…With the aim to test this hypothesis, our group conducted an experiment that did not show the influence of stress in our experimental groups. Thus, this hypothesis was not confirmed by our experimental data, which are in accordance with other studies that used the same restraint method (results not shown) (17,18).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…With the aim to test this hypothesis, our group conducted an experiment that did not show the influence of stress in our experimental groups. Thus, this hypothesis was not confirmed by our experimental data, which are in accordance with other studies that used the same restraint method (results not shown) (17,18).…”
Section: Discussionsupporting
confidence: 56%
“…Rats were immobilized in a plastic cylinder that allowed access to all four limbs for the application of acupuncture needles (17,18). This apparatus permits acupuncture stimulation in awake rats.…”
Section: Immobilization and Electroacupuncture Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Immobilization (2 h) for 13 consecutive days was able to reduce the immobilizationinduced c-Fos expression in most brain structures, including amygdala, hypothalamus, thalamic nuclei, and cortical areas (Medeiros et al, 2003). In this sense, the wide effect of repeated stress can be related to the fact that the habituation acted simultaneously in many circuits independently of which neurotransmitters or intracellular mechanisms were involved.…”
Section: Overviewmentioning
confidence: 98%
“…Stereological methods were not employed in this study due to potential bias associated with counts generated in this manner, such as uncertainties as to the extent to which antiserum penetrates through the thickness of the tissue sections and difficulties in defining the boundaries of the several cell groups of interest. Moreover, our interest was to make only relative comparisons of the strength of Fos induction as a function of the treatment status (Li and Sawchenko, 1998;Medeiros et al, 2003).…”
Section: Cell Counting and Statistical Analysismentioning
confidence: 99%